Effects of Different Exogenous Organic Substrates on Soil Carbon and Nitrogen Mineralization and Their Priming Effects - Chaoran Sun; Shaohui Tan; Zhihua Qiu; Songlin Sun; Ping Jiang; Limei Chen (Agronomy, 2023)
The input of exogenous organic matter could affect the transformation of soil carbon (C) and nitrogen (N), and their C- and N-priming effects (CPE and NPE) play a key role in the balance of soil C and N. However, little is known about how the interaction effect between straw and straw biochar regulates CPE and NPE. Therefore, we conducted a 90-day incubation experiment, which included five treatments: no straw and straw biochar (CK), 1.5% straw (S), 0.53% straw biochar (B), 1.5% straw + 0.53% straw biochar (SB), and 1.5% straw + 1.06% straw biochar (SB1). Our findings revealed that cumulative soil CO2 emissions were increased by 95.52–216.53% through the short-term input of exogenous organic matter input; however, this trend gradually weakened with decreasing dissolved organic C (DOC) content. The cumulative NPE generated by the addition of exogenous organic matter was much smaller than the cumulative CPE. Under the B and S treatments, the cumulative CPE and NPE were negative throughout the entire incubation period. The SB treatment remarkably boosted the microbial biomass nitrogen (MBN) content; however, the SB1 treatment was more effective in inhibiting soil C and N mineralization processes than SB treatment. Moreover, the cumulative CPE and NPE were mainly regulated by N. We conclude that the combination of straw and straw biochar preferentially stimulated soil C mineralization, but that this effect decreased with time, which may be due to the consumption of labile DOC caused by the initial positive CPE, while soil N mineralization had a lag effect.